Hexavalent Chromium Exposure Induces Intestinal Barrier Damage via Activation of the NF-κB Signaling Pathway and NLRP3 Inflammasome in Ducks - Xing, Chenghong; Yang, Fan; Lin, Yiqun; Shan, Jiyi; Yi, Xin; Ali, Farah; Zhu, Yibo; Wang, Chang; Zhang, Caiying; Zhuang, Yu; Cao, Huabin; Hu, Guoliang (Frontiers in Immunology, 2022)
Hexavalent chromium [Cr (VI)] is a dangerous heavy metal which can impair the gastrointestinal system in various species, however, the processes behind Cr (VI)-induced intestinal barrier damage are unknown. 48 healthy 1-day-old ducks were stochastically assigned to four groups and fed a basal ration containing various Cr (VI) dosages for 49 days. Results of the study suggested that Cr (VI)-exposure could significantly increase the content of Cr (VI) in the jejunum, increase the level of diamine oxidase (DAO) in serum, affect production performance, cause histological abnormalities (shortened of the intestinal villi, deepened crypt depth, reduced and fragmentated of microvilli) and significantly reduced the mRNA levels of intestinal barrier-related genes (ZO-1, Occludin, Claudin-1 and MUC2) and protein levels of ZO-1, Occludin, Claudin-1, resulting in intestinal barrier damage. Furthermore, Cr (VI) intake could increase the contents of hydrogen peroxide (H2O2) and malondialdehyde (MDA), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-18 (IL-18), but decrease the activities of total-superoxide dismutase (T-SOD), catalase (CAT) and glutathione reductase (GR); up-regulated mRNA levels of TLR4, MyD88, NF-κB, TNFα, IL-6, NLRP3, Caspase-1, ASC, IL-1β and IL-18 and protein levels of TLR4, MyD88, NF-κB, NLRP3, Caspase-1, ASC, IL-1β and IL-18 in the jejunum. In conclusion, Cr (VI) could cause intestinal oxidative damage and inflammation in duck jejunum by activating the NF-κB signaling pathway and the NLRP3 inflammasome.